ANALISIS PROFITABILITAS USAHA INDUSTRI RUMAH TANGGA KERIPIK CAP IKA DI KOTA DUMAI - Siti Zulaikha; Suarman '; Rina Selva Johan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Business type chips industry is one of the micro enterprises which are currently very interested by most people in the city Dumai. Increasing public interest snack chips into a potentiality huge market opportunity to earn large profit. When it will open a bussines in the domestic industry chips, one most consider the profitability, is how the business’s ability to generate profits that will be a picture of the effectiveness of business. The purpose of this study was to determine the lever of profitability of micro enterprises domestic industry type chips. Population in this study is the domestic industry in the distric Cap Ika Dumai sestern city Dumai. This method uses a method in which the saturated samplepopulation sampled directly. Data collection techniques is through interview. Data analysis techniques using the technique of the average net income, profitability and calculation return on assets ( ROA ). The results showed that the average household net profit industry cap Ika chips in the city as whole amounted Dumai are Rp 21.244.286,- . that is equal to the highest operating profitability 46% and return on assets are 75% so t. At capital can be restored as well as the return on assets was also rated quite hight.Keywords : Profitability, micro-enterprises, micro enterprises type of industry chips.